Coagulation and fibrinolysis after moderate and very heavy exercise in healthy male subjects - Weiss, Claus; Seitel, Günther; Bärtsch, Peter (Medicine and science in sports and exercise, 1998)
To examine the relationship between exercise intensity and activation of coagulation and fibrinolysis, we measured markers of thrombin, fibrin, and plasmin formation in 12 male subjects (mean 24 ± 4 yr (SD)) before and after running on a treadmill for 1 h at two different intensities corresponding to moderate (82% maximal heart rate (HR), 68%˙VO2max) and very heavy (94% maximal HR, 83% ˙VO2max) exercise. During moderate exercise plasma levels of tissue plasminogen activator (t-PA) antigen rose from 3.7 ± 0.5 (mean ± SE) to 14.6± 1.8 ng·mL-1 (P < 0.01) and of plasmin-α-antiplasmin (PAP) complexes from 2.1 ± 0.3 to 4.2± 0.7 nmol·L-1 (P < 0.01), whereas prothrombin fragment 1+2 (PTF1+2), thrombin-antithrombin III (TAT) complexes and fibrinopeptide A (FPA) did not change significantly. In response to very heavy exercise, mean plasma levels of t-PA antigen and PAP complexes exceeded the upper limit of normal values 2.5- (P < 0.01) and two-fold(P < 0.01), respectively, while significant increases of plasma levels of PTF1+2 (P < 0.01), TAT (P < 0.05), and FPA(P < 0.01) occurred within the range of normal. We conclude that in healthy young individuals, exercise-induced activation of coagulation is well balanced by activation of the fibrinolytic system, since moderate exercise results in increased plasmin formation only, while at very heavy exercise generation of plasmin seems to exceed that of thrombin and fibrin.